Contaminantes emergentes: Azocorantes e PBTAs - Graciani, Fernanda Silva [UNESP] (My University, 2014)
Being irreplaceable to keep all the sources of life in our planet, the water is one of the most important natural resource on Earth. The textile industries are responsible for the liberation of huge quantities of effluents in the environment, and consequently, responsible for a big caption of water. Knowing that the same water used by the textile industries is the same water that holds a quantity of life in the environment and fills the populations, made this research paper due to upgrade some of the important parts in toxicology of azodyes and its derivates (PBTAs non Cl PBTAs) and so to warn about the damages this dyes can be to the environment and so to the human beings.
Emerging contaminants: Azodyes and PBTAs
Keywords: Environment; Textile dyes; Water quality